2017
DOI: 10.3171/2016.10.focus16364
|View full text |Cite
|
Sign up to set email alerts
|

Impact of cervicothoracic region stereotactic spine radiosurgery on adjacent organs at risk

Abstract: OBJECTIVE Stereotactic radiosurgery (SRS) of the spine is a conformal method of delivering a high radiation dose to a target in a single or few (usually ≤ 5) fractions with a sharp fall-off outside the target volume. Although efforts have been focused on evaluating spinal cord tolerance when treating spinal column metastases, no study has formally evaluated toxicity to the surrounding organs at risk (OAR), such as the brachial plexus or the oropharynx, when performin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 70 publications
(15 reference statements)
0
3
0
Order By: Relevance
“…Commonly occurring as an acute or sub-acute event, VCF is a frequent complication of spinal SBRT that has been reported in 3–39% of patients [7], [8], [9], [10], [31], [32], [33], [34], [35]. Cunha et al [9] analyzed 167 spMets in 90 patients who received single-fraction 20−24 Gy SBRT, or 18−35 Gy in 2−5 fractions of SBRT, and observed 12 (63%) and 7 (37%) cases of de novo and progressed VCF, respectively, with a median time to SBRT-induced VCF of 3.3 months.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Commonly occurring as an acute or sub-acute event, VCF is a frequent complication of spinal SBRT that has been reported in 3–39% of patients [7], [8], [9], [10], [31], [32], [33], [34], [35]. Cunha et al [9] analyzed 167 spMets in 90 patients who received single-fraction 20−24 Gy SBRT, or 18−35 Gy in 2−5 fractions of SBRT, and observed 12 (63%) and 7 (37%) cases of de novo and progressed VCF, respectively, with a median time to SBRT-induced VCF of 3.3 months.…”
Section: Discussionmentioning
confidence: 99%
“…In spite of its aforementioned advantages, implementation of high-dose radiation to the spine may induce vertebral compression fractures (VCF), which are reported to develop more commonly (3–39%) than the most serious complication of radiotherapy, namely, myelopathy (1–5%) [7], [8], [9], [10], [11], [12]. Given the negative impact of VCF on patients’ quality of life even in the absence of progressive disease, the prevention and/or timely diagnosis and treatment of VCF are of paramount importance in patients undergoing SBRT for spMets [13], [14].…”
Section: Introductionmentioning
confidence: 99%
“…One trial on NSCLC has suggested the possibility to push these constraints even further, reporting no toxic events with D max 78 Gy in 1.8-2-Gy-fractions (BED 3,max ¼ 125-130 Gy) [14] . To our knowledge, RIBP post SBRT has been limitedly addressed in the literature [4,[26][27][28][29][30]. Based on 36 patients with seven cases of RIBP, Forquer et al [4] estimated the 2-year-risk Figure 3.…”
Section: Discussionmentioning
confidence: 99%